2013
DOI: 10.1016/j.cyto.2013.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis infection results in a modest pro-inflammatory cytokine response and a decrease in T cell chemokine secretion in human polarized endocervical epithelial cells

Abstract: The endocervical epithelium is a major reservoir for Chlamydia trachomatis in women, and genital infections are extended in their duration. Epithelial cells act as mucosal sentinels by secreting cytokines and chemokines in response to pathogen challenge and infection. We therefore determined the signature cytokine and chemokine response of primary-like endocervix-derived epithelial cells in response to a common genital serovar (D) of C. trachomatis. For these studies, we used a recently-established polarized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
46
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 93 publications
13
46
2
Order By: Relevance
“…Polarized human endometrial epithelial cells also secrete more IL6 apically, although IL6 accumulates in the basolateral compartment constitutively and following treatment with LPS [26]. Polarized epithelial cells from other mucosa, including the cervix, intestine, and respiratory tract also principally secrete IL6 apically, but IL6 is also detectable basolaterally [47][48][49]. However, the findings in the present study of an exclusive release of IL6 apically and the absence of detectable IL6 in the basolateral compartment appear unique to bovine endometrial epithelial cells.…”
Section: Vectorial Il6 From Endometrial Epitheliumcontrasting
confidence: 56%
“…Polarized human endometrial epithelial cells also secrete more IL6 apically, although IL6 accumulates in the basolateral compartment constitutively and following treatment with LPS [26]. Polarized epithelial cells from other mucosa, including the cervix, intestine, and respiratory tract also principally secrete IL6 apically, but IL6 is also detectable basolaterally [47][48][49]. However, the findings in the present study of an exclusive release of IL6 apically and the absence of detectable IL6 in the basolateral compartment appear unique to bovine endometrial epithelial cells.…”
Section: Vectorial Il6 From Endometrial Epitheliumcontrasting
confidence: 56%
“…IFNγ was quantified by a cytometric bead array assay (MILLIPLEX MAP Immunology Multiplex Assay). Millipore, Billerica, MA) as previously described (Buckner et al, 2011, 2013). Total indoles were quantified using Salkowski's test (Salkowski, 1885), modified as described by Szkop et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Buckner et al (35) reported that infection of human polarized endocervical cells by virulent chlamydiae resulted in only a modest increase in proinflammatory cytokines, leading these investigators to propose that chlamydiae may in fact be stealth pathogens using evasion strategies to circumvent proinflammatory cytokines and T cellactivating chemokines. Considering that natural chlamydial infection of humans is caused predominantly by plasmid-bearing organisms and results in reinfection or persistent infection, an accumulative proinflammatory and immunomodulatory host response might be sufficient to produce an enhanced damaging inflammatory response and a concomitant decreased ability to immunologically control infection in time.…”
Section: Discussionmentioning
confidence: 99%